1993
DOI: 10.1021/bi00069a025
|View full text |Cite
|
Sign up to set email alerts
|

Conformational behavior of Escherichia coli OmpA signal peptides in membrane mimetic environments

Abstract: Nuclear magnetic resonance and circular dichroism (CD) studies of isolated peptides corresponding to WT and mutant OmpA signal sequences are reported; all of the peptides adopt substantial amounts of alpha-helical structure both in 1:1 (v/v) trifluoroethanol (TFE)/water and in sodium dodecyl sulfate (SDS) micelles. In TFE/water, the helix begins after the positively charged N-terminal residues and is most stable in the hydrophobic core, which correlates with results obtained previously for other signal sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 73 publications
12
170
0
Order By: Relevance
“…Comparison of the conformation of the peptide in two different micelle systems by comparing the secondary structure-sensitive interresidue NOE cross-peaks was hampered by cross-peak overlap problems and by quantification difficulties due to dynamical effects. The intensities of the medium range NOEs for p25 are relatively low compared with those for the bacterial signal peptides of OmpA [34] or PhoE [35] associated with similar micelles. This can be explained by the fact that p25 is less hydrophobic than the bacterial signal peptides, resulting in a dynamical equilibrium between water-soluble (random coil) and micelle-bound (~-helicab forms of p25.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Comparison of the conformation of the peptide in two different micelle systems by comparing the secondary structure-sensitive interresidue NOE cross-peaks was hampered by cross-peak overlap problems and by quantification difficulties due to dynamical effects. The intensities of the medium range NOEs for p25 are relatively low compared with those for the bacterial signal peptides of OmpA [34] or PhoE [35] associated with similar micelles. This can be explained by the fact that p25 is less hydrophobic than the bacterial signal peptides, resulting in a dynamical equilibrium between water-soluble (random coil) and micelle-bound (~-helicab forms of p25.…”
Section: Resultsmentioning
confidence: 85%
“…It has been shown that the difference between the Ha proton chemical shifts in a protein structure and the chemical shifts in a random coil also correlates with protein secondary structure. An s-helix [34]. For p25 in the presence of DPC micelles, the differences between the Ha chemical shift values with respect to those in water, are given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] The helix content is highest, and the helix is most stable in the hydrophobic core of the signal sequence. 12,15,16 When the helical conformation required in the targeting pathway was not revealed by these studies, the intrinsic tendency of signal sequences to fold into an a-helix was established.…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…6), consistent with formation of highly populated helical structure. From the mean C"H shifts, we estimate an average population of 75% helix from Trp 7 to Ala 22 and 57% helix between His 24 and Phe 33 Rizo et al, 1993). From both the C"H chemical shifts and the daN(ir i + 3) NOEs, there appears to be a break in the helix at Ala 22 and Gly 23.…”
Section: Nmr Spectramentioning
confidence: 99%